Prevalence and determinants of inadequate dietary diversity among pregnant women in four Sub-Saharan Africa countries: a multilevel analysis of recent demographic and health surveys from 2021 to 2022 - Zegeye, Alebachew Ferede; Mekonen, Enyew Getaneh; Tamir, Tadesse Tarik; Workneh, Belayneh Shetie (Frontiers in Nutrition, 2024)
Background: Diversity in the mother's diet can have major effects on the developing fetus throughout pregnancy. Approximately one million neonates die on their first day of life as a result of inadequate nutrition throughout pregnancy, which also complicates the mother's pregnancy and has a negative impact on the delivery outcome. Prevalence and determinants of inadequate dietaryDietary diversity during pregnancy areis poorly recognized in developing countries, despite the fact that it is detrimental. As a result, the objective of this research wasstudy aimed to evaluateassess the prevalence and contributingassociated factors of inadequate dietary diversity in four Sub-Saharan African countriesBurkina Faso, Ghana, Kenya, and Tanzania among pregnant women.Methods: Secondary data analysis was conducted using data from the most recent Demographic and Health Surveys, which included four countries in Sub-Saharan Africa between 2021 and 2022. A total of 80,083 pregnant women were included in this study. The women's dietary diversity was computed from 10 food categories. Based on the minimum diversity score, women were categorized as having inadequate dietary diversity if their diversity score was less than five food items and as having adequate dietary diversity if they took five or more food groups. A multilevel mixed-effects logistic regression model was used to identify the factors associated with inadequate dietary diversity. At p-values <0.05, significant factors correlated with inadequate diversity were identified. The result was interpreted using 95%CI and adjusted odds ratio. The best-fit model was determined to be the one with the lowest deviance and highest loglikelihood ratio.Results: More than nine out of 10 women who were pregnant in this study had inadequately varied diets.The prevalence of inadequate dietary diversity among pregnant women in Burkina